The Large Uterus Classification System: a prospective observational study. (8th June 2021) - Uccella, S; Kho, RM; Garzon, S; Casarin, J; Zorzato, PC; Ghezzi, F
Abstract : Objective: To investigate the Large Uterus Classification System (LUCS) ability to predict surgical outcomes and complications in total laparoscopic hysterectomies (TLHs) for large uteri. Design: Prospective observational study. Setting: Two referral centres. Population or sample: Three hundred and ninety‐two women who underwent TLH for a large uterus (uterine fundus at or over the transverse umbilical line). Methods: Between 2004 and 2019, the intraoperative LUCS was estimated in all patients. The LUCS considers the uterine and adnexal vascular pedicles displacement. Type 1 is without vascular pedicles displacement. Type 2 has the cephalad displacement of adnexal vascular pedicles. The uterine vessels displacement regardless of adnexal pedicles defines Type 3. Main outcome measures: Patients' characteristics with perioperative outcomes were prospectively collected and compared between the three types of large uteri. Results: Two hundred and fifty‐one (64%), 82 (20.9%) and 59 (15.1%) women had Type 1, Type 2 and Type 3 uteri, respectively. Women with Type 1 uteri had a lower uterine weight, shorter operative time, less blood loss and lower complication rates than women with Types 2 and 3. The conversion rate to laparotomy in Type 1 was similar to that in Type 2 (odds ratio [OR] 0.98; 95% CI 0.32–3.56) but lower than Type 3 (OR 0.35; 95% CI 0.14–0.97); in Type 2 it was lower than Type 3, although without the conventional statistical significance (OR 0.36; 95% CI 0.13–1.13; P  = 0.07). Multivariable analysis showed that the uterine Type (1 versus 2–3) was independently associated with the total complications rate (OR 2.00; 95% CI 1.09–3.68; P  = 0.02). Conclusions: The LUCS appears associated with surgical outcomes and complications, potentially stratifying the surgical risk and guiding the surgical technique in TLHs for large uteri. Tweetable abstract: The Large Uterus Classification System may predict outcomes in total laparoscopic hysterectomy of large uteri. Tweetable abstract: The Large Uterus Classification System may predict outcomes in total laparoscopic hysterectomy of large uteri.